The Warning on Saturated Fat: From Defective Experiments to Defective Guidelines - Dayrit, Fabian M (Archīum Ateneo, 2017)
Coconut oil has been adversely affected by the current dietary guidelines that advocate a lowering of total fat and the replacement of saturated fat with polyunsaturated fat. This recommendation has its origins in the saturated fat-cholesterol-heart disease hypothesis that Ancel Keys first proposed in 1957. This hypothesis became an official recommendation with the publication of the Dietary Guidelines for Americans in 1980 and has been adopted by many other countries and international agencies. The dietary recommendations also warn against coconut oil. Recently, the American Heart Association re-issued this warning in its 2017 Presidential Advisory. However, a critical review of the experiments that Keys conducted has revealed experimental errors and biases that cast serious doubt on the correctness of his hypothesis and the warnings against coconut oil. Further, the recommendation to decrease saturated fat recommendation effectively means an increase in unsaturated fat in the diet. The actual result has been an increase in omega-6 fats and a high omega-6 to omega-3 fat ratio. This unhealthy ratio has been linked to heart disease, the very disease that the AHA wants to target, as well as cancer and inflammatory diseases. Defective experiments have led to defective guidelines. This first paper in this series of papers will present these errors and biases and address the points raised by the AHA.